DIGITAL WELLBEING IN HYBRID LEARNING ENVIRONMENTS: BALANCING ACADEMIC PERFORMANCE AND MENTAL HEALTH - Catherine Li; Andres Villanueva; Josefa Flores; Noorhani Dyani Laksmi (Journal Neosantara Hybrid Learning, 2026)
The widespread institutionalization of hybrid learning environments has intensified student exposure to digitally mediated academic demands, generating mounting concern among educators, policymakers, and mental health professionals regarding the cumulative effects of prolonged screen engagement, boundary dissolution between academic and personal digital spaces, and algorithmically driven distraction on student psychological wellbeing and academic performance outcomes. Existing frameworks for digital wellbeing have been developed predominantly for general consumer technology contexts and remain insufficiently theorized for the specific cognitive, emotional, and social demands of hybrid educational settings. This study aims to examine the relationship between digital wellbeing practices, academic performance, and mental health outcomes among students engaged in hybrid learning environments across tertiary educational institutions. A sequential explanatory mixed-methods design was employed, combining a quantitative survey administered to 624 undergraduate students across four universities with qualitative interviews conducted with 36 purposively selected participants, analyzed through structural equation modeling and reflexive thematic analysis respectively. Digital wellbeing practices significantly predicted both academic performance (? = 0.512, p < .001) and mental health outcomes (? = 0.467, p < .001), with screen boundary management and purposeful technology disengagement emerging as the strongest protective factors. Intentional digital wellbeing integration within hybrid learning design substantially reduces psychological distress while sustaining academic performance, necessitating institution-level policy commitments beyond individual student self-regulation.